Characterization and performance of biofuel from passion fruit processing residues - Nakorn Tippayawong (2018)
© 2012 Newswood Limited. All rights reserved. Passion fruit seeds are a byproduct from juice production. Oils were extracted from the passion fruit seeds, and transesterified to produce biodiesel with KOH as a catalyst. The obtained biofuel was characterized for its fuel properties in accordance with the Thai and international standards. Constant speed tests were also carried out to evaluate performance of the biofuel against petro-diesel in a small, unmodified, compression ignition engine. Analysis showed that the quality of biodiesel obtained was within the limits set by the Thai and American biodiesel specifications. Engine test results revealed that performance based on engine torque and power between petro-diesel and biodiesel was comparable. The biofuel appeared to have higher efficiency and lower CO emission than petro-diesel.